Credit rating and adverse selection cost - Ocvia Freriana (2008)
This report examines the impact of issuer rating changes on adverse selection components of the bid ask spread. In order to obtain the value of adverse selection components, we make use of four spread decomposition models, i.e., Glosten and Harris (1988), Lin et al. (1995), Madhavan et al. (1997), and Huang and Stoll (1997). We evaluate the impact of issuer rating changes by performing time series analysis, one sample t-test, and independent & paired samples t-test.